THE IMPLEMENTATION OF THE DEATH PENALTY AGAINST NARCOTICS TRAFFICKERS FROM THE PERSPECTIVE OF CRIMINAL LAW IN INDONESIA AND THAILAND - Nazli, Muhammad Qardhawi; Lubis, Mhd. Teguh Syuhada (Law Jurnal, 2024)
Drug trafficking is a global threat that damages social order and public health, including in Indonesia and Thailand. The enforcement of criminal procedural law is the main instrument in combating drug traffickers, but it often clashes with human rights principles. This study aims to evaluate the effectiveness of the application of the death penalty against drug traffickers in both countries from a criminal law perspective. This research uses a qualitative method with a comparative approach, analyzing legal regulations, enforcement policies, and their impact on human rights in Indonesia and Thailand. The results show that although both countries have strict laws to deal with drug traffickers, their implementation faces serious challenges, such as violations of legal procedures, torture practices, and the imposition of the death penalty that triggered international criticism. In Indonesia, despite legal reform efforts, implementation of human rights remains weak, while Thailand adopts a repressive approach that often ignores the principles of justice. In conclusion, the effectiveness of criminal procedure law enforcement against drug traffickers in both countries still needs to be improved to align with human rights principles. This research recommends human rights-based legal reform and strengthening oversight mechanisms in the criminal justice process.